Estimating equilibrium exchange rates / John Williamson. - Williamson, John (Institute for International Economics, 1994)
The problems of exchange rate misalignments and the resulting payments imbalances have plagued the world economy for decades. At the Louvre Accord of 1987 the Group of Five industrial countries adopted a system of reference ranges for exchange rate management, influenced by proposals of C. Fred Bergsten and John Williamson for a target zone system. The reference range approach has, however, been operated only intermittently and half-heartedly, and questions continue to be raised in policy and scholarly circles about the design and operation of a full-fledged target zone regime.